Digitalization of the Banking Sector and Performing Analysis in the World and Turkey - ÇELİK, S.Buket; MANGIR, Fatih (Cyberpolitik Journal, 2020)
Technological developments such as Generation-5 technology, artificial intelligence, smartphones and robots, big data, blockchain technology, augmented reality, software engineering, cybersecurity provide great opportunities for the bank sector. The banking sector is trying to integrate its customers into this process by performing its services over the internet on global scale. Since the first A.T.M. was installed in 1982, digital transformation has started in Turkey, and later there has been a significant transformation engaged in the banking sector. Through the innovations such as ATM, Pos device, credit card, mobile banking, artificial intelligence, the Turkish banking system transformed from traditional banking to internet banking has launched some strategies by placing the digitalization at the center of its corporate strategies. The number of customers use at least once the internet banking in Turkey between 2006 and 2020, has reached 13 million 253 thousand people in June 2020 from 3 million 367 thousand in 2006. In this study, the concept and context of digital banking is discussed and the outlook of digitalization in banking sector will be provided for the world and Turkey.